Workers' perception of reports of sub-standard acts and conditions - Molocho Herrera, Ronald Arcenio (2023)
The main objective of the study was to determine the perception that the workers of an industrial maintenance company have about the reports of substandard acts and conditions (RACSE). It consisted of a descriptive cross-sectional study of a single box, the sample consisted of 30 workers. The survey was used as a technique and as an instrument a questionnaire with 21 items for the perception variable. The statistical program SPSS 26 was used to determine the reliability of the questionnaire through Cronbach's alpha (0.960). According to the results obtained, it was concluded that there is a moderately favorable level of perception in 100% regarding the use of the RACSE, In addition; the qualifications by dimension yielded the following results: for the knowledge dimension, it was moderately favorable in 63.3% (19); for the resources dimension, it was favorable in 43.3% (13); for the environment dimension, it was unfavorable in 46.7% (14); for the motivation dimension, it was moderately favorable in 73.3% (22); for the attitude dimension, it was moderately favorable in 76.7% (23); for the participation dimension, it was 56.7% (17) and for the leadership dimension, it was favorable by 46.7% (14).